2022
DOI: 10.3390/genes14010075
|View full text |Cite
|
Sign up to set email alerts
|

Loss of Mitochondrial Genetic Diversity despite Population Growth: The Legacy of Past Wolf Population Declines

Abstract: Gray wolves (Canis lupus) in the Iberian Peninsula declined substantially in both range and population size in the last few centuries due to human persecution and habitat fragmentation. However, unlike many other western European populations, gray wolves never went extinct in Iberia. Since the minimum number was recorded around 1970, their numbers have significantly increased and then stabilized in recent decades. We analyzed mitochondrial genomes from 54 historical specimens of Iberian wolves from across thei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 84 publications
1
9
0
Order By: Relevance
“…This is particularly relevant given the long‐term isolation of Iberian wolves from other European populations (Silva et al., 2020). The recent loss of diversity is consistent with previous evidence based on mitogenomes of Iberian wolves (Salado et al., 2023) and other central European populations (Dufresnes et al., 2018), indicating that the most substantial decline in mitochondrial diversity occurred in recent times, largely due to the systematic and intense persecution of wolves since the 19th century (Boitani, 1995). This view is also supported by the longer HBD segments found in the genome of contemporary Iberian wolves that originated from inbreeding events occurring four or two generations ago, corresponding to the post‐bottleneck period.…”
Section: Discussionsupporting
confidence: 89%
“…This is particularly relevant given the long‐term isolation of Iberian wolves from other European populations (Silva et al., 2020). The recent loss of diversity is consistent with previous evidence based on mitogenomes of Iberian wolves (Salado et al., 2023) and other central European populations (Dufresnes et al., 2018), indicating that the most substantial decline in mitochondrial diversity occurred in recent times, largely due to the systematic and intense persecution of wolves since the 19th century (Boitani, 1995). This view is also supported by the longer HBD segments found in the genome of contemporary Iberian wolves that originated from inbreeding events occurring four or two generations ago, corresponding to the post‐bottleneck period.…”
Section: Discussionsupporting
confidence: 89%
“…Genetic similarity between the historical French wolves and contemporary individuals may also suggest that the current wolf expansion from Italy through the Alps may enable a partial recreation of the gene pool of the original French population. Recent studies of the Iberian wolves showed that despite the population expansion and stable population size in the last decades, the mitochondrial genetic diversity is still declining (Salado et al, 2022). Therefore, although the wolf population in France is in recovery, the close genetic monitoring of the expanding populations is important, as this population may still be of conservation concern.…”
Section: Discussionmentioning
confidence: 99%
“…The long‐term wolf population decline increased in rate in the past few centuries due to extermination by humans and habitat loss and was associated with reductions in geographic range. This process was particularly intense in Western Europe, where the species became locally extinct by the end of the 19th century, with the exception of the Iberian Peninsula and Italy, resulting in drastic loss of genetic diversity (Dufresnes et al, 2018; Salado et al, 2022). In contrast, in Eastern Europe, where demographic declines were less severe, genetic diversity remained stable throughout the late 19th and 20th centuries (Dufresnes et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…However, the relatively high level of heterozygosity of wolves of the RK does not mean that the population is welfare. This can be ensured by the specific transit position of the territory, the absence of natural barriers, continuous connection with neighboring populations, the diversity of the initial population, and at the same time against the background of a possible loss of allelic and mitochondrial diversity (Jędrzejewski et al, 2005; Salado et al 2022). For example, in Finland, according to Jansson et al (2014), about 20% of microsatellite alleles were not found in the modern population in comparison with historical samples.…”
Section: Discussionmentioning
confidence: 99%